Metode Analisis Wacana Dalam Media Sosial - Anjelin Rahmi Junaidi Harahap; Muhammad Fathurrahman Al-Anshori; Kartini Kartini (Dakwatussifa: Journal of Da'wah and Communication, 2022)
Discourse analysis is a field of study that examines the meanings conveyed by a person's words, sentences, or other utterances, whether they are spoken out or written down. According to Fairclough, discourse has three outcomes. Discourse, in the first place, aids in the formation of social identity and subject position. Both discourses contribute to the formation of interpersonal relationships. Thirdly, discourse has a role in the formation of knowledge and belief structures. Particularly in the Industrial Revolution 4.0 Era, when the internet has evolved into one of the most fundamental human necessities, social media development is accelerating. Social engagement takes place not only in person, but also frequently online or virtually. The public is quite fond of a number of social media sites, including Facebook, Twitter, Instagram, Pinterest, Tiktok, and others. Keywords: Analysis, Discourse, Social Media